In Vlogs We Trust: Consumer Trust in Blog and Vlog Content - Lockie, Maree Alice (Auckland University of Technology, 2019)
In the digital age we live in, consumers seek out product information from their online peers via electronic word-of-mouth information platforms such as blogs and vlogs. Vlogs (i.e. video blogs) are typically hosted on online video-sharing sites such as YouTube. Some vloggers attract hundreds of thousands or even millions of followers, which has spawned a new approach to consumer persuasion, influencer marketing (Glucksman, 2017). However, although consumers trust online user-generated product information as if it were similar to word-of-mouth from their offline networks of friends and family, this online information omits one key basis of trust in traditional word-of-mouth: personally knowing the information provider (Dichter, 1966). Thus, this thesis seeks to discover why it is consumers trust blog and vlog content despite the consumer not personally knowing the blogger or vlogger. Secondly, the thesis addresses the question whether there are any differences in the factors that influence trust in blog content versus trust in vlog content. Social Exchange Theory provides a theoretical basis for this research, whereby consumers and bloggers/vloggers enter into an exchange relationship. Content creators seek intrinsic satisfaction and extrinsic monetary or status benefits, whilst content audiences seek entertainment and information benefits as well as consumer information that reduces purchase risks. Thus, there is an exchange of knowledge and entertainment for viewership, which results in satisfaction, status and money for the content creator – a reciprocal exchange. An exploratory sequential mixed methods design was employed. First, qualitative in-depth interviews were conducted with 10 blog readers and vlog viewers, as well as three industry personnel involved in content creation. Based on the qualitative interviews, a model was created of the key influences on consumer trust in blog and vlog content. Next, an online survey was conducted with 300 USA blog readers and vlog viewers to test this model, using structural equation modelling. Exploratory factor analysis was run on the initial data set to ensure scale measures were reliable and valid, followed by a process of confirmatory factor analysis and structural modelling. The study concludes that amongst the many characteristics of blogs and vlogs, what truly influences consumer trust in blog and vlog content is a parasocial relationship that develops between the consumer and the content creator. This relationship is influenced most strongly by content authenticity, content attractiveness, personal content (that is, self-disclosure by the content creator), and the provision of product information. The research concludes that consumers trust blog and vlog content because they feel that they know the content creator; they have a relationship with the content creator, albeit a one-sided relationship. This research contributes to the body of marketing knowledge by illustrating how and why consumers trust blog and vlog content; and by identifying that parasocial relationships exist between consumers and online content creators in video- and text-based channels. For managers, this research highlights the importance of matching target markets to content creators for successful marketing. As consumers form relationships with their favourite content creators, managers need to understand their target markets and the content creators most attractive to these markets.
Keywords: Blog; Vlog; Content creators; Authenticity; Parasocial; Trust; eWOM; WOM; Consumer information